Public trust in the long-term care insurance pilot program in China: An analysis of mediating effects - Peng, Rong; Zhang, Wansha; Deng, Xueqin; Wu, Bei (Frontiers in Public Health, 2022)
Objective: This study aimed to evaluate the implementation of the long-term care insurance (LTCI) pilot program in China through an examination of public trust in the system. Method: An online survey was used to collect data from 786 participants in the city of Guangzhou, one of the pilot sites of the LTCI. Ordinal logistic regression models were used to investigate the related factors of public trust in the LTCI. Structural equation modeling (SEM) was conducted to test the mediating effect of satisfaction with LTCI policy on the relationship between insurance awareness and public trust. Results: More than 60% of participants gave a positive evaluation of the LTCI pilot program. More than 70% of the participants recognized the important role of the program. Both an understanding of insurance and satisfaction with LTCI policies were associated with public trust. The proportion of the indirect effect with regard to the total effect of satisfaction on trust was 70.133%, greater than the direct effect of 29.867%. Conclusions: Satisfaction with the LTCI program played an important mediating role between insurance awareness and public trust. LTCI policy optimalization is recommended to improve public trust in LTCI program.